Assessment of roadside concentration of PM2.5 at the U.P. Centennial Dormitory - Perez, Jose Ma. Albert H.
The concentration of particulate matter with diameter sizes of 2.5 micrometers or less (PM2.5) was measured for 72 hours in front of the U.P. Centennial Dormitory along C.P. Garcia Avenue. The major source of this pollutant is identified to be vehicle traffic and for that reason a traffic volume count was conducted simultaneously. A perception survey was also conducted to assess the level of exposure to PM2.5 of the dormitory residents. The 24-hour average PM2.5 concentration was compared with the local as well as the international guideline values at 75 ug/ml and 25 ug/ml, respectively. The March 19, 20, and 21 , 20 15 monitoring dates in front of the U.P. Centennial Dormitory were measured to have 24-hour average PM2.5 concentrations of 55.52 ug/ml, 54.33 ug/ml. and 27.91 ug/ml, respectively. These observed values barely passed the local and ultimately failed the international guideline values. Results of the perception survey showed that 84.06% of the respondents have experienced at least one of the symptoms associated with air pollution hence further studies are recommended. A linear regression analysis was conducted and resulted to positive correlation values for the observed hourly average PM2.5 concentrations and the total traffic volume as well as the traffic volume of diesel-engine type and gasoline-engine type. The highest correlation, with a value of 0.70, resulted when a 20-minute lag time was considered between the hourly average PM25 concentrations and the total traffic volume.